The Influence of Digitalization on the Practice of Pancasila Moral Values in Private Business Vocational School Students Al-Washliyah 3 Medan - Alwi Irwanto; Ulian Barus (PT Inovasi Pratama Internasional, 2023)
This research aims to determine whether there is an influence of digitalization on the practice of Pancasila moral values among students at the Al-washliyah 3 Medan Private Business Vocational School. Digitalization is the term for a wave of information technology which was initially based on analogue and print media to become digital based using digital technology and data. Pancasila moral values are a guideline for social life in society. In other words, Pancasila moral values are procedures for good social behavior among society. The form of this research is quantitative research and the approach method is product moment correlation, namely looking for the level of influence of digitalization on the practice of Pancasila moral values among students at Al-Washliyah 3 Medan Private Business Vocational School. The population in this study was all students in class XI of Al-washliyah 3 Medan Private Business Vocational School with a sample of 31 students. The instruments used in this research were questionnaires and interview guides as well as observation sheets only to strengthen the questionnaire data. Meanwhile, researchers sought research results by distributing questionnaires to students as respondents and a questionnaire with 20 questions on each variable. The data analysis technique in this research uses the product moment correlation formula and hypotheses using significance tests. The results of this research show that there is a strong influence between digitalization and the practice of Pancasila moral values. This can be seen by the correlation coefficient value of 0.702 when measured by the measurement results of the correlation coefficient interpretation table which states that the correlation coefficient value is included in the value of 0.60-0.799 and the relationship is stated to be strong. Next, the hypothesis was tested for variable significance with a significance ratio of 0.05.